PROGRAM LATIHAN SELF-COMPASSION UNTUK REMAJA SEBAGAI UPAYA PENINGKATAN KESEHATAN MENTAL DAN KESEJAHTERAAN - Rachmawati, Nur Cahya; Priihastuti, Mizan; Annarahayu, Luthfi; Isnugroho, Hernawan; Istiqomah, Istiqomah; Rachelli, Cindy Aulia (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2025)
Adolescents face various physical, psychological, and social pressures that may affect mental health. Self-compassion is an effective approach to improve adolescents’ mental well-being. This community service program aimed to enhance understanding and skills of self-compassion through interactive workshops and practical exercises for 25–30 adolescents aged 13–17 years. The program was conducted over three days, including introduction sessions, mindfulness exercises, positive affirmations, self-reflection, and discussion and sharing sessions. Evaluation was conducted using pre- and post-program questionnaires, direct observation, and daily reflections. Results indicated an increase in the average questionnaire score from 22 to 34 (54%), active participation in exercises, and improved emotional management. Participants’ reflections also showed the formation of positive habits supporting mental well-being. This program demonstrates that participatory and interactive self-compassion exercises are effective in building emotional resilience and positive behaviors among adolescents.